ANALISIS KEBIJAKAN ALIH FUNGSI LAHAN PERTANIAN KE NON – PERTANIAN DI KABUPATEN KLATEN TAHUN 2013-2016 (Studi Kasus Kecamatan Ceper Kabupaten Klaten) - Fattah, Arsianita Nur; Purnomo, Eko Priyo (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2018)
This study aims to find out some aspects of agricultural function transfer in Kecamatan Ceper Klaten regency. The magnitude of the number of functions transfer in Klaten Regency affects the economic level of the population. This condition prompted many farmers to sell their agricultural land. Supervision related to the transfer of agriculture function to the non-agricultural sector in Klaten Regency needs to be adjusted to see the control done by Klaten Regency Government, Agricultural Service of Klaten Regency and Ceper District Government toward agriculture transfer policy to non-agriculture in Klaten Regency. The purpose of this study is to find out how they can use agriculture and agriculture in Klaten District together with their driving factors. This research uses case study research with a qualitative method. The focus of the research is on the analysis for the conversion of agricultural land to non-agricultural land. The result of data analysis obtained from Agricultural Service of Klaten Regency, National Land Agency of Klaten Regency, Environment Agency of Klaten Regency and Government of Sub-District of Ceper in the implementation of agriculture is not necessarily optimal done by some driving factors. Suggestions to be given are: (1) optimizing the existing Rules and policies to be carried out in accordance with the rules (2) Optimizing Agricultural Extension activities (3) improving and socializing for related offices and farmers to know. to non-agriculture (4) further education and land improvement (5) the immediate refresher of data on paddy fields and their final (6) controls provide benefits to farmers who have managed their farms well.